Understanding the spatial trajectories of minority groups: An approach that examines their demographic, cultural and socio-economic characteristics - Philip Sapiro (Comparative Population Studies (CPoS), 2019)
Population researchers have contributed to the debate on minority group distribution and disadvantage and social cohesion by providing objective analysis. A plethora of new distribution measurement techniques have been presented in recent years, but they have not provided sufficient explanatory power of underlying trajectories to inform ongoing political debate. Indeed, a focus on trying to summarise complex situations with readily understood measures may be misplaced. This paper takes an alternative approach and asks whether a more detailed analysis of individual and environmental characteristics is necessary if researchers are to continue to provide worthwhile input to policy development. Using England and Wales as a test bed, it looks at four small sub-populations (circa 250,000 at the turn of the century) - two based on ethnic grouping: Bangladeshi and Chinese; and two based on an under-researched area of cultural background, religion: Jews and Sikhs. Despite major differences in longevity of presence in the UK, age profile, socio-economic progress, and levels of inter-marriage, there are, at a national level, parallels in the distribution patterns and trajectories for three of the groups. However, heterogeneity between and within the groups mean that at a local level, these similarities are confounded. The paper concludes that complex interactions between natural change and migration, and between suburbanisation and a desire for group congregation, mean that explanations for the trajectory of distribution require examination of data at a detailed level, beyond the scope of index-based methods. Such analyses are necessary if researchers are to effectively contribute to future policy development.
urn:nbn:de:bib-cpos-2019-13en5
Keywords: 300; Spatial distribution; Index of dissimilarity; Ethnic group; Religion; Migration; Natural change